A contratação temporária dos agentes socioeducativos no Espírito Santo: necessidade ou estado de exceção permanente? - Araújo, Tayane de Castro (2018)
The governance paradigm of contemporary states is the permanent exception, according to Giorgio Agamben. With a discourse based on the need for immediate action, they justify attitudes based on legal exceptions, legitimizing a position in which it is decided without being based on the rule for the concrete case, and delegated that decision to the force of a law. The privileged example used in this work is the temporary contracting of the socio-educational agents of the State of Espírito Santo. The Federal Constitution of 1988 rules that the public services offered by the State must be performed by agents duly approved in a public contest. However, clause IX of article 37 of the same constitutional provision brings the exception to this rule, providing that in the case of exceptional public interest, transient and unavoidable need can be removed from this norm and hired on a temporary basis, even without prior approval in the competition.Based on this proviso, in Espírito Santo, most of the socio-educational agents are hired. It will be noted that this legal exception is used in a recurring manner, which would characterize the adoption of exceptional principles that are not the purpose of the constitutional norm, and therefore, does not have the legal requirement. Thus they exclude the rule, and become more effective than the general precept, configuring this as its force of law. Assuming this position, it is perceived that the State approached a governmental model based on the permanent exception. For this, we used the bibliographical research and the hermeneutic-dialectical method to analyze in a more profound way this event that occurs in the state of Espirito Santo, just like this discourse of necessity not only does not correspond to the resolution of the problems that justify the exception, but also manifests an abuse of the state power.